COMPARISON EFFECT BETWEEN PEGAGAN (Centella asiatica) EXTRACT AND PRAMIPEXOLE TOWARD LOCOMOTOR ACTIVITIES, α - SYNUCLEIN, AND NRF2 EXPRESSION IN ZEBRAFISH PARKINSON MODEL - Trisnawati, Ayu; Anasrulloh, Anasrulloh; Rianawati, Sri Budhi; Khotimah, Husnul; Ali, Mulyohadi; Susetya, Budi (Malang Neurology Journal, 2019)
Background: Parkinson disease is characterized with deposition of Lewy Bodies containing α–synuclein happened due to the effect of chronic neuroinflammation that causes the death of dopaminergic neurons through oxidative stress processes, so it involves the response of Nuclear factor erythroid 2-like 2 (Nrf2). Centella asiatica  (C.asiatica) contains antioxidant effect, inhibits the aggregation of α–synuclein and improves the locomotor on Parkinson-model animals so it needs to compare to the standard medication.Objective: To compare the C. asiatica extract and Pramipexole to the zebrafish Parkinson model by determining the locomotor activity, α–synuclein expression, and Nrf2.Methods: This study used six groups of zebrafish: negative control, rotenone rotenone [5 μg/L], pramipexole1, 2, 3 (rotenone + pramipexole [3,5] ng/mL, [7] ng/mL, [14] ng/mL), and C. asiatica(rotenone + C. asiatica [10] μg/mL). The observations of locomotor activity of day 0, 14, and 28 were continued to the α–synuclein immunohistochemical examination, and Nrf2 on the midbrain area.Results: There are significant differences in locomotor activity on day 28 among the C. asiatica group with rotenone (p<0,05), while there are no significant differences among the C. asiatica group with pramipexole [7] ng/mL and [14] ng/mL (p>0,05). α–synuclein expression of the C. asiatica group is the lowest and significantly different from all groups (p<0,05), while Nr2 had no significant differences (p>0,05).Conclusion: C. asiatica extract [10] μg/mL is equal to pramipexole [7] ng/mL and [14] ng/mL in improving locomotor activity, but C. asiatica extract holds excellence as it decreases α–synuclein expression better than pramipexole, while Nrf2 expression shows no differences.